Evaluating the Performance of Information Technology Systems and its Effect on Achieving Quality Banking Performance (Applied Research on a Sample of Private Banks( - Abd Al-sahib Najim Abd; Raghib Fakri Atya (Journal of Madenat Alelem University College, 2021)
This research aims to shed light on the need for bank departments to continuously evaluate the performance of the information technology systems applied in the bank, through which it seeks to evaluate the efficiency and effectiveness of management in the use of information technology resources towards achieving banking goals, and the need of senior management to technical standards and measurement mechanisms for a purpose helping it to determine the points of deficiency and weakness in performance and take the necessary measures to address it in a manner that ensures improving performance and upgrading the quality of services provided to customers. Suggested criteria have been prepared based on the standard specifications and procedures mentioned in (I SO / IEC 20000, 38500) for the purpose of evaluating the performance of banks for the year 2019, data and information were collected and analyzed for a sample of banks (Middle East Bank, National Islamic Bank), and in light of the application process a number of conclusions were reached, most notably, that the application of standards. The proposal leads to improving the performance of banking information technology systems in a manner that ensures the bank’s provision of its products and services with a high level of quality. The researchers presented a number of recommendations, the most prominent of which is the need for the bank’s interest in applying quality standards related to information technology, including specifications (ISO/IEC20000,38500( , as well as The need for banks to use auditors and consultants Holders of certified allergic certificates in the field of information technology.